134k views
3 votes
Just rationalize and simplify

Just rationalize and simplify-example-1

2 Answers

7 votes

Answer:

(a+5)-4√(a+1) /(a-3)

Explanation:

√(a+1) - 2 / √(a+1) + 2

={√(a+1) - 2 }{√{(a+1) - 2 } / {√(a+1) + 2} {√(a+1) - 2 }

={√(a+1) - 2 }² / {√(a+1)}² - 2²

=[ {√(a+1)}² -4√(a+1) +4 ] / a+1-4

=[a+1-4√(a+1)+4] / (a-3)

=(a+5)-4√(a+1) /(a-3)

User DrowsySaturn
by
5.1k points
3 votes


\mathsf{Given :\;\;(√(a + 1) - 2)/(√(a + 1) + 2)}


\mathsf{Multiplying\;Numerator\;and\;Denominator\;with\;√(a + 1) - 2,\;We\;get :}


\mathsf{\implies ((√(a + 1) - 2)(√(a + 1) - 2))/((√(a + 1) + 2)(√(a + 1) - 2))}}


\mathsf{\implies ((√(a + 1) - 2)^2)/((√(a + 1))^2 - (2)^2)}}


\mathsf{\implies ((√(a + 1))^2 + (2)^2 - 2(√(a + 1))(2))/(a + 1 - 4)}}


\mathsf{\implies (a + 1 + 4 - 4√(a + 1))/(a + 1 - 4)}}


\mathsf{\implies (a + 5 - 4√(a + 1))/(a - 3)}}

User Caramba
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.